Supramolecular Nanofibrillar Thermoreversible Hydrogel for Growth and Release of Cancer Spheroids. (30th November 2016) - Li, Yunfeng; Khuu, Nancy; Gevorkian, Albert; Sarjinsky, Sharon; Therien‐Aubin, Heloise; Wang, Yihe; Cho, Sangho; Kumacheva, Eugenia
Abstract: Growth of three‐dimensional cancer spheroids (CSs) in man‐made hydrogels mimicking natural extracellular matrix is an important and challenging task. Herein, we report on a supramolecular temperature‐responsive hydrogel designed for the growth and subsequent release of CSs. A filamentous hydrogel was formed at 37 °C from an aqueous suspension of cellulose nanocrystals surface‐functionalized with temperature‐responsive polymer molecules. The encapsulation of cells in the hydrogel enabled effective growth of CSs with dimensions determined by the concentration of cellulose nanocrystals in the hydrogel. On demand release of CSs without loss of cell viability and spheroid integrity was achieved upon hydrogel cooling. The tumorigenic properties of the released CSs were examined by encapsulating and re‐growing them in fibrin hydrogel. The results in this work can be used in fundamental cancer research and in cancer drug screening.